MULTICARRIER TRAPEZOIDAL PWM STRATEGIES FOR A SINGLE PHASE FIVE LEVEL CASCADED INVERTER - R. BENSRAJ; S. P. NATARAJAN (Journal of Engineering Science and Technology, 2010)
This paper presents a novel approach for controlling the harmonics of output voltage of chosen Cascaded Multilevel Inverter (CMLI) employing trapezoidal PWM switching strategies. Carrier Disposition (CD) methods and Phase Shift (PS) method employed are evaluated using spectrum of the output voltage and other performance measures such as crest factor, form factor etc and the use of inverter state redundancies to perform additional application specific control tasks such as power flow control from each DC source. This paper focuses on Multicarrier Trapezoidal PWM (MCTPWM) techniques with Phase Disposition (PD), Phase Opposition Disposition (POD), Alternative Phase Opposition Disposition (APOD) and PS of carrier for the chosen CMLI. Simulations are performed using MATLAB/SIMULINK. Harmonic analysis and evaluation of performance measures for various modulation indices have been carried out. It is observed that PD method provides output with the lowest distortion. Of the four strategies developed, POD is found to perform relatively better since it provides relatively higher fundamental RMS output voltage and relatively lower stress on the devices for moderate modulation index.